Emotion Dysregulation as a Prospective Predictor of Suicidal Ideation in an at-Risk Mixed Clinical Sample. (31st August 2020) - Raudales, Alexa M.; Short, Nicole A.; Schmidt, Norman B.
Abstract : The current study tested whether emotion dysregulation predicts suicidal ideation over the course of 6 months. Community members (N = 298) with elevated suicide risk completed a clinical interview and self-report questionnaires at baseline and month-6 follow-up appointments. Elevated general emotion dysregulation but not subscales significantly predicted increases in suicidal ideation at month-6 follow-up after accounting for initial suicidal ideation, treatment condition, and negative affectivity. Furthermore, general emotion dysregulation as well as lack of awareness and lack of clarity subscales were significantly associated with prior suicide attempts at baseline after accounting for negative affectivity. Findings support the establishment of emotion dysregulation as a risk factor for suicidal ideation and provide evidence for a role in suicide attempts. Findings call for the development of interventions targeting emotion dysregulation in effectively predicting and preventing suicidality.